Long-term quality of life and clinical outcomes in patients with resistant hypertension treated with renal denervation - Agata Krawczyk-Ożóg; Tomasz Tokarek; Katarzyna Moczała; Zbigniew Siudak; Artur Dziewierz; Waldemar Mielecki; Tomasz Górecki; Karolina Gerba; Dariusz Dudek (Advances in Interventional Cardiology, 2016)
Introduction: Pharmacological treatment combined with lifestyle modifications is an effective treatment for arterial hypertension. However, there are still patients who do not respond to standard treatments. Patients with pharmacologically resistant hypertension may benefit from renal denervation (RDN). Aim: To assess long-term quality of life (QoL) after RDN and effectiveness in reduction of blood pressure (BP) in patients with resistant hypertension. Material and methods: From 2011 to 2014, 12 patients with previously diagnosed resistant hypertension, treated by RDN, were included in this study. The QoL was assessed using a standardized Polish version of the Nottingham Health Profile questionnaire (NHP). Results : The median age was 54 (IQR: 51–57.5) years. Mean baseline ambulatory pre-procedural systolic/diastolic BP was 188/115 ±29.7/18 mm Hg. The mean values of systolic/diastolic BP measured perioperatively and 3, 6, 12 and 24 months postoperatively were 138/86, 138/85, 146/82, 152/86, and 157/91. All p-values for mean systolic and diastolic BP before versus successive time points after RDN were statistically significant; p-value for all comparisons < 0.05. Improvement of QoL was only observed in two sections of the NHP questionnaire: emotional reaction and sleep disturbance. The analysis of the NHP index of Distress (NHP-D) showed a lower distress level perioperatively and 3, 6, 12 and 24 months after RDN as compared to baseline. The RDN was not associated with any significant adverse events. Conclusions : Patients with pharmacologically resistant hypertension treated with RDN achieved significant reduction in BP during 24-month follow-up. Furthermore, a significant improvement in the QoL was observed in those patients.